Sterol C-22 Desaturase ERG5 Mediates the Sensitivity to Antifungal Azoles in Neurospora crassa and Fusarium verticillioides - Sun, Xianyun; Wang, Wenzhao; Wang, Kangji; Yu, Xinxu; Liu, Jie; Zhou, Fucai; Xie, Baogui; Li, Shaojie (Frontiers in Microbiology, 2013)
Antifungal azoles inhibit ergosterol biosynthesis by interfering with lanosterol 14α-demethylase. In this study, 7 upregulated and 4 downregulated ergosterol biosynthesis genes in response to ketoconazole treatment were identified in Neurospora crassa. Azole sensitivity test of knockout mutants for 6 ketoconazole-upregulated genes in ergosterol biosynthesis revealed that deletion of only sterol C-22 desaturase ERG5 altered sensitivity to azoles: the erg5 mutant was hypersensitive to azoles but had no obvious defects in growth and development. The erg5 mutant accumulated higher levels of ergosta 5, 7-dienol relative to the wild type but its levels of 14α-methylated sterols were similar to the wild type. ERG5 homologues are highly conserved in fungal kingdom. Deletion of Fusarium verticillioides erg5 also increased ketoconazole sensitivity, suggesting that the roles of ERG5 homologues in azole resistance are highly conserved among different fungal species, and inhibition of ERG5 could reduce the usage of azoles and thus provide a new target for drug design.